Nitric oxide functions in the heart - Tarik Kivrak; Kenan Erdem; Ilgin Karaca (Archives of Anatomy and Physiology - Peertechz Publications, 2017)
Nitric oxide (NO) is an important organizer of the cardiovascular function and is an important mechanism in hampering the pathogenesis of the diseased heart. The scenario of bioavailable NO in the myocardium is complicated: 1) NO obtain from both endogenous and exogenous NO synthases (NOSs) and the number of NO from exogenous sources varies considerably. 2) NOSs are located at separated regions of cardiac cells and are organized by varied ways under stress.3) NO arranges various target proteins via different ways of post-transcriptional modification which are soluble guanylate cyclase [sGC]/cyclic guanosine monophosphate [cGMP]/protein kinase G [PKG]-dependent phosphorylation, S-nitrosylation, and trans-nitrosylation. 4) the downgradient stabilizers of NO differ from proteins and enzymes in the mitochondria and membrane.5) NOS generates several radicals in addition to that NO (varied NO-associated yields) and stimulates redox responses. But, NOS inhibits cardiac oxidases to diminish the sources of oxidative stress in diseased hearts. Recent consensus indicates the importance of nNOS protein in cardiac protection under pathological stress and NO-dependent mechanisms are better understood in healthy and diseased hearts.